Web app for the monitoring of pregnant and puerperal women: technological production. - da Silva, Lenise Dutra; Bär, Karen Ariane; de Oliveira Zamberlan, Alexandre; Dal Ben, Luiza Watanabe; Dal Sasso, Grace Marcon; Backes, Dirce Stein (Online Brazilian Journal of Nursing, 2022)
Objective: To describe the production process of a web app prototype to monitor pregnant and puerperal women. Method: A technological production study, of the prototyping type, developed in five stages: Identification of the relevance of an app for the online monitoring of pregnant and puerperal women with the participation of two users and nine professionals; prototype modeling; prototyping validation; and design and implementation of the app in its online version. Results: The app has proved to be a technological tool that is easy, fast and safe to access, as well as an important ally in the virtual care of pregnant and puerperal women, minimizing exposure and waiting time in emergency services and professional offices. Conclusion: The web app has expanded users' adherence to the prenatal, childcare and postpartum consultations, providing a new space for the nurses' professional practice.